Community Empowerment Through Aquaponics: Sustainable Innovation For Environmental Welfare And Local Economy: Pemberdayaan Masyarakat Melalui Akuaponik: Inovasi Berkelanjutan Untuk Kesejahteraan Lingkungan Dan Ekonomi Lokal - Maylius, Puti; Rahmat Hidayat; Giorfinn Tsabit Cygna (KPN Kopertis X, 2024)
This abstract summarizes the scope, objectives, methods, data, results and main conclusions of research on community empowerment through the implementation of the Aquaponics Program. This research aims to evaluate the impact of the program on the welfare of the environment and local economy. The research methodology includes data collection through field observations, interviews, and data analysis to assess program effectiveness. The research results show that the Aquaponics Program has succeeded in empowering the community by providing efficient and sustainable agricultural alternatives. This system not only increases local food production but also reduces negative impacts on the environment. In addition, this program makes a positive contribution to the local economy by increasing market access and diversifying income sources. The main conclusion is that the Aquaponics Program is not only an agricultural innovation, but also a model of sustainable community empowerment. The implications of this research can be used as a basis for the development of supporting policies and the expansion of similar programs to achieve sustainable development goals.